Seeking No War, Achieving No Peace: The Conflict over the Siachen Glacier - Tommy Andersson; Conan Mukherjee (Lund University, School of Economics and Management, Department of Economics, 2018)
This paper models "no war, no peace" situations in a game theoretical framework where two countries are engaged in a standoff over a military sector. The first main objective is to identify rational grounds for such situations and, more precisely, explicit equilibria that leads to such situations. It is demonstrated that both countries get the same payoff from being in this continuous state of perpetual hostility and, moreover, that "no war, no peace" situations can be explained only if the countries perceive an equal measure of military advantage by controlling the area. Given this insight, the second objective of the paper is to provide insights about how "no war, no peace" situations can be resolved. Two different pathways are suggested. The first is idealistic and based on mutual trust whereas the second is based on deterrence meaning that both countries impose a threat of using armed force against the other country in their respective military doctrines.
Keywords: C73; H56; 330; game theory; infinite horizon game; stationary strategies; Siachen conflict